An unusual cause of biliary obstruction: a case report - Matthews, Bethany K.; Palamuthusingam, Pranavan (International Surgery Journal, 2024)
Abdominal aortic aneurysms are considered as an unusual cause of extraductal biliary obstruction with less than 30 case studies found within the literature. This case report will discuss an 81-year-old female with an incidental initially asymptomatic finding of extrahepatic biliary obstruction and gallbladder distension secondary to an abdominal aortic aneurysm in routine computed tomography staging scan. Extraductal biliary obstructions can require alternative or additional interventions to that of treatment for intraductal obstruction. Subsequently, the aetiology of biliary obstruction is important for clinicians to consider and recognise, to allow for the implementation of appropriate and timely management.